Factors contributing to delay in seeking treatment among pulmonary tuberculosis patients in Suneka Sub-County, Kenya - Nyatichi, Fena Ondeki; Amimo, Fred A.; Nabie, Bayoh; Ondimu, Thomas O. (Health Education Research & Development, 2016)
Tuberculosis is a major global public health problem and a leading cause of morbidity and mortality in Kenya. TB control has remained a major challenge for the TB control programme especially in this HIV/AIDS era and the emergence of multi-drug resistant TB (MDR-TB). Early identification of cases and commencement of effective chemotherapy is an effective method to control the spread of TB. Reliance on passive case finding means that patients play a key role in reducing delay to diagnosis and treatment. Patient delay (duration from onset of symptoms to first contact with a health care provider at a public health facility) is a major challenge to TB control and is dependent on several factors. The purpose of this study was to determine the duration from onset of symptoms to seeking appropriate TB treatment among pulmonary TB (PTB) patients and investigate the factors associated with patient delay in Suneka sub-County, Kisii County, Kenya. A cross-sectional survey, using a semi-structured questionnaire, was carried out at five public health facilities in the sub-County. Data entry, management and analysis were done using SPSS Version 15. The mean patient delay and associations between length of patient delay and the various independent variables was determined. Multiple logistic regression was performed to determine the factors independently associated with patient delay. The mean patient delay was 54 days and 65.4% of the study subjects had delayed for more than 30 days. Delay in seeking appropriate TB treatment among PTB patients in Suneka sub-County was associated with poor perception of services in public health facilities (OR=4.91; CI=1.6-15.3; P=0.0061), visiting a private clinic (OR=4.24; CI=1.5-11.6; P=0.0052) and stigma (OR=2.46; CI=1.9-12.2; P=0.0178). Most PTB patients in Suneka sub-County delay in presenting at public health facilities after the onset of major TB symptoms and the main factors responsible for this delay include having a poor perception of the quality of services offered in public health facilities, prior attendance at a private clinic and stigma associated with the disease. Delay was not found to be associated with the patient socio-demographic characteristics, knowledge of TB, distance or transport cost to the nearest public health facility. Since TB services are integrated in the general health care system, the findings highlight the need by the Ministry of Health (MOH) to improve service delivery at public health facilities and thereby encourage patients to seek early diagnosis and treatment of communicable diseases or reduce patient delays. Educational campaigns should go beyond providing general information about TB to emphasize embracing a positive attitude of transmission reduction through early treatment.
Keywords: Delay; Treatment; Pulmonary tuberculosis; Patients